Playing for Dollars: Labor Relations and the Sports Business - Dabscheck, Braham (Relations industrielles / Industrial Relations, 1996)
The article reviews the book, "Playing for Dollars: Labor Relations and the Sports Business," 3rd edition, by Paul D. Staudohar.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Professional sports; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Sports